THE EFFECTIVITY OF CONTEXTUAL TEACHING AND LEARNING BASED ONLINE LEARNING IN TERM OF MATHEMATICAL REPRESENTATION AND DISPOSITION OF JUNIOR HIGH SCHOOL - Ninda Karisa; Endang Listyani (Jurnal Pedagogi Matematika, 2023)
This research is aims to know (1) the effectiveness of contextual teaching and learning based online learning in term of mathematical disposition of junior high school students, (2) the effectiveness of contextual teaching and learning based online learning in term of mathematical representation of junior high school students. The type of the research is quasy experiment with One- Group Pretest-Posttest Design. This research applies online learning with the help of Whatsapp group class application as a media communication between students and teachers. The subjects of this study were 29 students of grade VII in Kroya Junior High School. The instruments that are used on this research are mathematical representation test and mathematical disposition questionaire. Hypotheses trial method uses One Sample Wilcoxon Signed -Rank Test, One Sample Binomial Test, and One Sample t-Test. Based on the result of hypotheses trial with a significance level of 5% concluded that: (1) contextual teaching and learning based online learning is effective in term of mathematical disposition of junior high school students, (2) contextual teaching and learning based online learning is effective in term of mathematical representation of junior high school students.